A fixed-time output feedback control scheme for double integrator systems. (June 2017) - Tian, Bailing; Zuo, Zongyu; Yan, Xiaomo; Wang, Hong
Abstract: A continuous output feedback control scheme rendering the closed-loop double integrator system globally stable in finite-time is presented. In particular, the convergence time is independent of initial conditions. The bi-limit homogeneous technique is used for controller and observer designs with fixed-time convergence. Then, a continuous output feedback control law is proposed for nominal double-integrator system and its perturbed version. The homogeneity and Lyapunov techniques are used to ensure the fixed-time stability of the closed-loop system under output feedback control framework. Finally, the efficiency of the proposed algorithms is illustrated by numerical simulations.